The Influence of Host Credibility, Hedonic Shopping Motivation, and Mobile App Usability on Impulsive Buying Behavior of Online Shopping App Users - Bekti Setiadi; Tyahya Whisnu Hendratni; Andriya Risdwiyanto; Sonya Sidjabat; Dana Aswadi; Yuliani Istiqomah (Dinasti Review, 2026)
The study is devoted to examining how host credibility, hedonic shopping motivation, and mobile app usability impact online shoppers' impulsive buying behavior. It is based on the growing incidence of impulse buying, which is largely the result of digital interaction and technology. A quantitative explanatory approach is utilized in the research, and purposive sampling is employed to select 200 active users of online shopping applications as respondents. Data is obtained through a five-point Likert scale questionnaire and subjected to multiple linear regression analysis. The results indicate that host credibility, hedonic shopping motivation, and mobile app usability are the main factors having a positive and significant impact on the consumers' impulsive buying behavior. Theoretical implications of this Study include the expansion of the digital consumer behavior research area through the integration of social, psychological, and technical factors. The findings also provide valuable insights for online retailers in the areas of digital marketing strategy and application development that could lead to more effective and sustainable impulse buying.